2019
DOI: 10.20945/2359-3997000000137
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation and heritability of markers of metabolic risk, physical activity, and physical fitness in nuclear families from Muzambinho (Minas Gerais, Brazil)

Abstract: Objective: This study investigated the familial aggregation and heritability of markers of metabolic risk, physical activity, and physical fitness in nuclear families from Muzambinho (Minas Gerais, Brazil). Subjects and methods: The study included members of 139 families, comprising 97 fathers (aged 40 ± 7 years), 129 mothers (35 ± 6 years), 136 sons (12 ± 4 years), and 121 daughters (12 ± 5 years). Evaluated markers included (A) body mass index, waist circumference, glycemia, and cholesterolemia, as metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Розрахований внесок спадковості в дисперсію показника ІМТ підлітків становить 41,4% (h 2 =0,41±0,09; p<0,001), що є досить високим показником і зіставним з показниками інших популяцій [7]. Внесок спадковості в дисперсію показника рухової активності в нашому дослідженні становить 23,1% (h 2 =0,23±0,07; p<0,001), що відповідає показнику, визначеному в дослідженні [6], автори якого визначили цей внесок на рівні 22% також за допомогою аналізу S.A.G.E.…”
Section: т а б л и ц яunclassified
See 1 more Smart Citation
“…Розрахований внесок спадковості в дисперсію показника ІМТ підлітків становить 41,4% (h 2 =0,41±0,09; p<0,001), що є досить високим показником і зіставним з показниками інших популяцій [7]. Внесок спадковості в дисперсію показника рухової активності в нашому дослідженні становить 23,1% (h 2 =0,23±0,07; p<0,001), що відповідає показнику, визначеному в дослідженні [6], автори якого визначили цей внесок на рівні 22% також за допомогою аналізу S.A.G.E.…”
Section: т а б л и ц яunclassified
“…Наслідування фізичної бездіяльності коливається від 22 до 60% у різних популяціях [5]. Поряд з цим внесок спадкових чинників у дисперсію індексу маси тіла (ІМТ) також значно коливається і за даними різних досліджень становить від 30 до 80% [6][7]. Варіативність впливу спадковості при вивченні ІМТ та РА демонструє значущість проведення досліджень у кожній окремій популяції з визначенням точок впливу на здоров'я населення.…”
unclassified
“…These factors include differences in the early shared (family) environment and differences in genetic makeup. Twin and family studies are in support of a significant role of genetic and shared environmental factors in the regulation of both physical activity behavior [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and early motor development [12,[33][34][35]. The heritability estimates of physical activity behavior strongly depend on the age of the child, with the shared (family) environment playing the largest role in childhood, but decreasing into adolescence, where genetic factors explain the largest part of variance in physical activity [18,36].…”
Section: Introductionmentioning
confidence: 98%
“…A meta-analysis by Kawasaki et al [5] also concluded that exposure to maternal hyperglycemia was associated with offspring obesity and abnormal glucose tolerance. Furthermore, familial factors have been considered as risk factors for MetS, including genetic and environmental factors shared among family members [3, 6, 7].…”
Section: Introductionmentioning
confidence: 99%